The ending of the canon: a canonical and intertextual reading of Revelation 21-22 - Tõniste, Külli (Library of New Testament studies, 2016)
Toward a methodology for a theological reading of Revelation -- Genre and literary structure of Revelation -- Intertextual vorbild of Revelation -- Revelation 21-22 as the ending of the canon -- Summary